A Comprehensive Performance Improvement Control Method by Fractional Order Control - Xi Zhou; Yao Mao; Chao Zhang; Qiunong He (IEEE Photonics Journal)
For the high precise tracking control task in quantum communications, this paper introduces a fractional-order control scheme to resolve the confliction between error rejection capacity and stability margin. In the system and controller design, a system preprocessing, including phase margin compensation and controller structure amelioration, is introduced to make the controller realizable. And in order to obtain the global optimum in controller parameter tuning, a visual version method is also imported. This innovative control scheme could effectively equilibrate the system's demands for high error suppression capacity and enough phase margin, and makes it possible for a class of systems’ high precision control. The innovative control method is experimented in an electro-optical system, which could help to obtain a better beam tracking performance in quantum communications.